2002
DOI: 10.2460/ajvr.2002.63.611
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vaccination on serum concentrations of total and antigen-specific immunoglobulin E in dogs

Abstract: Vaccination of dogs for rabies increases serum concentrations of total IgE and induces IgE specific for vaccine antigens, including tissue culture residues. Vaccination history should be considered in the interpretation of serum total IgE concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 35 publications
0
9
1
Order By: Relevance
“…FCS contains a variety of proteins including BSA, fibrinogen, lipoprotein, macroglobulin, and transferrin. Although it was reported that vaccination with rabies vaccine induced the elevation of the serum IgE specific to the vaccine antigens including BSA and bovine fibronectin in some healthy dogs (Hogenesch et al, 2002), at present, there has been no data on the specific protein(s) included in FCS to cause allergic reactions after vaccination in dogs. Further studies are necessary to identify the causative protein(s) included in FCS that induce allergic reactions after vaccination in dogs.…”
Section: Discussionmentioning
confidence: 98%
“…FCS contains a variety of proteins including BSA, fibrinogen, lipoprotein, macroglobulin, and transferrin. Although it was reported that vaccination with rabies vaccine induced the elevation of the serum IgE specific to the vaccine antigens including BSA and bovine fibronectin in some healthy dogs (Hogenesch et al, 2002), at present, there has been no data on the specific protein(s) included in FCS to cause allergic reactions after vaccination in dogs. Further studies are necessary to identify the causative protein(s) included in FCS that induce allergic reactions after vaccination in dogs.…”
Section: Discussionmentioning
confidence: 98%
“…(iii) Cross-reacting antibodies induced by other infectious agents, associated with the poor health status of dogs in field conditions may interfere with the antibody assay technique. In addition, rabies vaccines produced on cell culture may contain cell contaminants, the latter can trigger the production of cell-specific antibodies by the vaccinated dogs [22]. ELISA plates are also coated with the rabies glycoprotein extracted from viral particles grown on cell culture.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, recent studies of the immunological consequences of routine rabies virus vaccination have shown that IgE antibodies might be generated to residual bovine molecules (e.g. bovine serum albumin, fibronectin) incorporated into vaccines (HogenEsch et al 2002). The clinical relevance of these antibodies has not been shown, but the potential exists for reactivity with the same bovine proteins of dietary origin.…”
Section: Spontaneously-arising Canine Dietary Hypersensitivitymentioning
confidence: 99%